2012
DOI: 10.1038/aps.2011.180
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic acid inhibits TNF-α-induced invasion of human prostate cancer PC3 cells in vitro through PI3K/Akt and NF-κB signaling pathways

Abstract: Aim: To investigate the mechanisms underlying the inhibitory effect of gambogic acid (GA) on TNF-α-induced metastasis of human prostate cancer PC3 cells in vitro. Methods: TNF-α-mediated migration and invasion of PC3 cells was examined using migration and invasion assays, respectively. NF-κB transcriptional activity and nuclear translocation were analyzed with luciferase reporter gene assays, immunofluorescence assays and Western blots. The ability of p65 to bind the promoter of Snail, an important mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…However, total Akt level remained unaltered for 48 hours. The overall trend was consistent with reports from points of Lü [44], but the peak of p-Akt occurred at 2 hours after treatment with TNF-α (10 ng/mL). The possible reasons to explain these differences are differences in concentration for TNF-α and study cells.…”
Section: Discussionsupporting
confidence: 90%
“…However, total Akt level remained unaltered for 48 hours. The overall trend was consistent with reports from points of Lü [44], but the peak of p-Akt occurred at 2 hours after treatment with TNF-α (10 ng/mL). The possible reasons to explain these differences are differences in concentration for TNF-α and study cells.…”
Section: Discussionsupporting
confidence: 90%
“…Gambogic acid (GA), a xanthonoid resin from Garcinia hurburyi tree, was able to inhibit tumor necrosis factor a (TNF-a)-induced invasion of PC3 cells in part via downregulation of Snail expression. 79 Another study has reported that the nontoxic phytochemical, silibilin, found in herbs such as milk thistle, decreased the levels of Snail and Slug, inhibited EMT and decreased migratory and invasive potential in PC3 and C4-2B prostate cancer cells. 80 Genistein, an isoflavonoid derived from soy products, when fed to transgenic adenocarcinoma mouse prostate model (TRAMP/FVB) mice, decreased the incidence of poorly differentiated cancer at the prostatic intra-epithelial neoplasia (PIN) stage.…”
Section: Therapies Targeting Snailmentioning
confidence: 99%
“…Previous studies have also identified the signal transduction pathways involved in regulating MMP-9 expression in various tumor cells (23,24). In particular, NF-κB is a significant transcription factor for regulating the MMP-9 gene promoter and contains NF-κB-binding sites (12). This study revealed that piceatannol regulates NF-κB activity by inhibiting p65 and p50 protein translocation.…”
Section: Discussionmentioning
confidence: 83%
“…A previous study demonstrated that the inhibition of NF-κB activity in human prostate cancer cells decreases their tumorigenic and metastatic abilities by suppressing angiogenesis and invasion via the downregulation of MMP-9 (11). Conversely, TNF-α stimulation results in NF-κB activation in prostate cancer cells and induces tumor invasion (12). Therefore, a potential strategy to suppress MMP-9-mediated tumor invasion is via the NF-κB pathway.…”
Section: Introductionmentioning
confidence: 99%